The Role of Knowledge Management in the Financial Performance of Small and Medium Companies - Zaid, Marwah I; Alqatrani, Russul Isam Noori; Alasadi, Hayder Ali (South Asian Journal of Social Sciences and Humanities, 2023)
This research aims to determine the effect knowledge management processes (knowledge generation, knowledge distribution, and application knowledge) on financial performance in the Malaysian small and medium companies. The descriptive analytical secondary and primary data was utilised as a tool for gathering data from 130 companies as a sample. The results display that there is a positive association among knowledge management with financial performance. The knowledge management represented in generation, distribute, and apply knowledge, and express it about performance through the perspectives of the financial perspective companies. As the research reached a set of conclusions, including that there the effect of knowledge management processes on raising level of performance.